Prophetic Approach dalam Kebijakan Pendidikan Indonesia: Studi Analisis Teori Sosial Profetik Kuntowijoyo - Alif Rizky Ramadhan; Lismawati (Universitas Muhammadiyah Prof Dr Hamka, 2022)
Indonesian education at this time has experienced a great shift from education that is oriented towards individual scientific capabilities to education that is oriented towards industrial needs. This shift occurred due to changes in the global market share which is increasingly fixated on industrial machines so that these ideas and thoughts develop in the national education ministry. As a result, the spirit of education in Indonesia is experiencing a void because the orientation and mindset that is currently being carried out is based on industrial needs. Seeing this condition, we as Muslims should realize the impact that arises from this industry-based education that is not supported by an understanding of the socio-religious approach and the religio-scientific approach. So it is not wrong if we re-read Kuntowijoyo's thoughts on prophetic social science as an alternative way of developing education based on a prophetic approach. So that Indonesian education does not only talk about industrial needs but also realizes how important the prophetic approach offered by Kuntowijoyo is as a driving force for educational development in Indonesia.